URBANISASI DAN KEGAGALAN REGENERASI PETANI DIBALIK MODERNISASI PERTANIAN DARI PERSPEKTIF KESEJAHTERAAN SOSIAL - ritonga, fajar (Politeknik Kesejahteraan Sosial Bandung, 2024)
The side effects of urbanisation and the failure of farmer regeneration behind the modernisation of agriculture for millennials in Indonesia have created social problems in urban areas. The purpose of this research is to describe the social problems of street children due to the urbanisation of both village youth and their parents from the village to Medan City. This research uses descriptive qualitative as an analytical knife, the research location is conducted in Medan City and selected places where street children usually do their activities as well as being informants in this research. The results of the study portrayed the village youth regarding farmers as unpromising and unprofitable jobs, when compared to the jobs of millennials today, despite the modernisation of agriculture. The problems arising from the migration of rural youth to the city who do not have skills and education become social problems including street children, vagrants, beggars, unemployment and result in the emergence of social pathology leading to criminality that requires handling from social workers. Keywords: Urbanisation, Social Problems, Agricultural Modernisation. Social Workers